COVID‐19 post‐vaccination lymphadenopathy: Report of cytological findings from fine needle aspiration biopsy. Issue 12 (25th August 2021) - Tan, Nicholas Jin Hong; Tay, Kai Xun Joshua; Wong, Soon Boon Justin; Nga, Min En
Abstract: The coronavirus COVID‐19 pandemic has spurred the rapid development of vaccines, with vaccination programmes already underway in many countries. Regional lymphadenopathy is one of the documented side effects of vaccination. We document the fine needle aspiration cytological findings of an enlarged supraclavicular lymph node in a 34‐year‐old Asian female following the first dose of the Pfizer‐BioNTech COVID‐19 mRNA vaccine, which appears to be the first such report in a premorbidly well patient with no known history of malignancy. The cytological findings featured a reactive pattern in keeping with follicular hyperplasia, with prominent germinal centre elements including lymphohistiocytic aggregates and tingible‐body macrophages. Despite an increased proportion of larger lymphocytes, the overall pattern was in keeping with a reactive pattern, bearing in mind the temporal and geographic relation to the vaccination injection. In instances of localised lymphadenopathy, particularly in supraclavicular or axillary locations, pathologists should be cognizant of the possibility of post‐vaccination reactive lymphadenopathy, and seek clinical and radiological hints favouring a benign process, whilst recognising potential morphological overlaps with lymphoproliferative disorders. Awareness of this diagnostic pitfall is especially important as COVID‐19 vaccination coverage is ramped up worldwide, leading to an expected increase in incidence of post‐vaccination reactive lymphadenopathy.